Post-Bronchoscopy Infections: A Literature Review: A Literature Review - Permatasari, Tri Wijayanti; Karuniawati, Anis (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2024)
Post-bronchoscopy infections are a critical concern in respiratory medicine, given their potential to exacerbate patient morbidity, particularly among immunocompromised individuals or those with pre-existing lung conditions, one of which is infection. The infection arises from lower respiratory tract pathogens, and most infections originate from reprocessing practices. Infection can occur when the bronchoscope comes into contact with the mucosa and blood vessels of the respiratory tract. Bacteremia is a more often post-bronchoscopy infection complication rather than pneumonia. It is commonly involving Coagulase-negative or positive Staphylococcus, non-hemolytic or hemolytic Streptococcus, Citrobacter species, and Klebsiella. However, in general, the incidence of post-bronchoscopy infection is mainly caused by gram-negative bacteria. Various risks can affect post-bronchoscopy infection that can increase the severity of the disease to death. It is important to increase obedience and precaution against the transmission of infection. Reducing bacterial pathogens and controlling infection are important steps to reduce the post-bronchoscopy infection mortality rate. Therefore, this study aimed to review the post-bronchoscopy infections in detail.